THE ROLE OF ROLE-PLAYING GAMES IN THE MORAL DEVELOPMENT OF PRESCHOOL CHILDREN (Archive of Conferences, 2020)
The spiritual development of a society depends on the content of its educational work. Therefore, there is a need for pedagogical interpretation of the reforms in preschool education, the system of step-by-step education in our country, to ensure the effective conduct of this process. Today we need to raise children to be perfectly developed in all respects, to have a broad outlook, creative thinking, intellectual potential. The education, spiritual maturity and ideological maturity of our young people, who are the future of our country, are among the urgent tasks of our time.